Temporal Trends in Parkinson’s Disease Related Mortality from 1999-2020: A National Analysis [version 1; peer review: 1 approved, 2 approved with reservations] - Balamrit Singh Sokhal; Thomas Shepherd; Christian Mallen; Sowmya Prasanna Kumar Menon; Amit Arora; Sara Muller (NIHR Open Research)
Introduction Parkinson’s disease (PD) is the most common neurodegenerative movement disorder and is associated with significant disability. The prevalence is rising, and studies have reported potential sex and race disparities in patient outcomes. Data about the demographic trends in PD-related mortality in the United States (US) is limited. This descriptive study aimed to report the national demographic trends in PD-related mortality over a 20-year period. Methods The US Centers for Disease Control and Prevention Wide-Ranging Online Data for Epidemiological Research (CDC-WONDER) Underlying Cause of Death database from January 1999 to December 2020 was used to determine the PD-related age adjusted mortality rate (AAMR) stratified by age, sex, ethnicity and geographic area, with the 1999 deaths as the reference group. Annual percentage change (APC) for AAMR was then calculated using Joinpoint regression. Results There were 515,884 PD-related deaths in the study period. The AAMR increased from 5.3 per 100,000 population in 1999 to 9.8 per 100,000 in 2020. Males had consistently higher AAMR than females and white race had consistently higher overall AAMR (7.6 per 100,000), followed by American Indians/Alaska Natives (4.4 per 100,000), Asians/Pacific Islanders (4.1 per 100,000) and Black/African Americans (3.4 per 100,000). The Midwest had the highest AAMR followed by West, South and Northeast. Utah, Idaho and Minnesota had the highest state-level AAMR. Conclusions This study identified significant age, sex, race and geographic disparities in PD-related mortality in the US. Older age, male sex, white race and Midwest locality were associated with the highest AAMR.